2002
DOI: 10.1002/path.1185
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of cyclin D1, E2F‐1, and Ki‐67 in benign and malignant thyroid lesions

Abstract: Cyclin D1 and E2F-1 proteins are essential for the regulation of the G1/S transition through the cell cycle. Cyclin D1, a product of the bcl-1 gene, phosphorylates the retinoblastoma protein, releasing E2F-1, which in turn activates genes involved in DNA synthesis. Expression patterns of E2F-1 protein in thyroid proliferations have not been reported. This study used monoclonal antibodies for cyclin D1 and E2F-1 proteins to immunostain sections of normal thyroid, hyperplastic (cellular) nodules, follicular aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
45
0
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 20 publications
5
45
0
4
Order By: Relevance
“…One puzzling common property of autonomous adenomas and papillary carcinomas is the down-regulation of a number of immediate early genes [NR4A1, JUNB (10), KLF10, and ZFP36]. Absence of upregulation may reflect the relatively low rate of cell proliferation in both tumors (42,43) and thus the low fraction of cells in early G 1 , but down-regulation is more difficult to explain.…”
Section: Discussionmentioning
confidence: 99%
“…One puzzling common property of autonomous adenomas and papillary carcinomas is the down-regulation of a number of immediate early genes [NR4A1, JUNB (10), KLF10, and ZFP36]. Absence of upregulation may reflect the relatively low rate of cell proliferation in both tumors (42,43) and thus the low fraction of cells in early G 1 , but down-regulation is more difficult to explain.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is necessary to point out that cyclin D3 may not be the only determinant of thyrocyte proliferation in human thyroid hyperproliferative diseases, since previous works have demonstrated that cyclin D1 is overexpressed in hyperplastic nodules and adenomas (Saiz et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The sections were counterstained with hematoxylin, and then scanned at low power to identify areas that were evenly stained. Estimates of the numbers of positive cells were scored as follows: negative, 0%; 1, 1-10%; 2, 11-25%; 3, 26-50%; 4, >50% positive (Saiz et al 2002). Two independent investigators performed the estimation.…”
Section: Immunohistochemical Analysismentioning
confidence: 99%